Validation of DSMC mass flow modeling for transsonic gas flows in micro-propulsion systems - Groll, R.; Frieler, T. (Frontiers in Mechanical Engineering, 2023)
In the present work, an inflow model for the DSMC method is presented and validated. The approach is based on inflow mass flow rate and temperature and is particularly suitable for arbitrary nozzle flow cases with higher density, subsonic inflow conditions. The validation is performed on a nozzle test case and the results are compared with experimental and numerical results based on DSMC and Navier-Stokes methods. Calculation of inflow and outflow boundary conditions on an analytical and numerical basis is presented. Results for axial and radial density, temperature, and pressure are in good agreement and reasonable relationships are obtained.Since only the inflow mass flow rate and temperature and the vacuum background pressure need to be known to apply the model, the calculation of the inflow velocity from analytical theory can be omitted, potentially eliminating possible sources of error resulting from theory-based calculations.